Implementación de un sistema de contabilidad de costos por órdenes de producción en el taller artesanal “Mary” de la ciudad de Latacunga, provincia de Cotopaxi durante el período enero-diciembre 2013 - Tipanluisa Cando, Sandy Valeria (2015)
This research is focused on the "Implementation of a Accounting Cost System for Production Orders in the Craft Workshop" Mary” in Latacunga city, Cotopaxi province during the period from January to December 2013. The methodology used in this research is an exploratory study through inductive an deductive method applied through facts observation in order to reach conclusions by applying some techniques an data collection instruments such as direct observation in the productive process to determine the procedures used in the making clothes. The surveys applied to employees, customers and suppliers of the craft workshop who are involved in the production and interview the owner of the workshop "Mary" making clothe with this technique a several analysis and interpretation the results. The implementation of accounting cost system for production orders includes the development of all records and documents filed in this research, so it allows an efficient control the transactions did during the financial period in order to determine the unit cost of the garments made in order to know the profit or loss that project.